Radioactivity, grade 11 : STEM road map for high school - Johnson, Carla C., 1969-; Walton, Janet B., 1968-; Peters-Burton, Erin E. (STEM road map curriculum series, 2019)
This uses project- and problem-based learning to help students understand the debate over the safety and efficiency of nuclear power for meeting the country's energy demands. Teams of students will apply what they learn about the science and history of nuclear energy to convey the views of particular stakeholder groups and propose solutions to the crisis.